Unraveling the film‐formation kinetics of interfacial polymerization via low coherence interferometry - Li, Weiyi; Liu, Xin; Li, Zhuo; Fane, Anthony G.; Deng, Baolin (AIChE journal, 2020)
Interfacial polymerization (IP) is one of the most important methods for fabricating thin film composite (TFC) membranes. Understanding the film‐formation mechanisms is of great value for developing membranes with enhanced performance. This work proposed a novel method to in situ characterize the film‐formation kinetics via low coherence interferometry (LCI). The polyamide film formed at the liquid–substrate interface was scanned in real time; the polymerization induced significant variations in the optical properties around the reaction zone. After mitigating the effects of the perturbed interface, the surface‐averaged intensity profiles provide a solid basis for analyzing the film‐formation kinetics at various depths. In particular, the effects of the monomer concentrations were investigated to reveal the asymmetric growth and development of irregular substructures. All the characterization results confirm that the LCI‐based characterization is a powerful tool for studying the structural evolution of the IP layer and thereby providing deeper insights for optimizing TFC membranes.